Development and Applications of Enhanced Green Fluorescent Protein Mutants - R.H. Stauber; K. Horie; P. Carney; E.A. Hudson; N.I. Tarasova; G.A. Gaitanaris; G.N. Pavlakis (BioTechniques)
The introduction of several mutations resulted in the generation of improved mutants of the green fluorescent protein (GFP). A strong green (GFPsg25) and blue (BFPsg50) fluorescent protein, gave 50-fold–100-fold brighter fluorescence compared to wild-type GFP and BFP (Tyr66His), respectively, upon expression in mammalian cells. GFPsg25 and BFPsg50 have different excitation and emission maxima. This allows their use as an efficient dual-color tagging system and their independent detection in living cells.